Identification of Candidate Susceptibility Genes to Puccinia graminis f. sp. tritici in Wheat - Henningsen, Eva C.; Omidvar, Vahid; Della Coletta, Rafael; Michno, Jean-Michel; Gilbert, Erin; Li, Feng; Miller, Marisa E.; Myers, Chad L.; Gordon, Sean P.; Vogel, John P.; Steffenson, Brian J.; Kianian, Shahryar F.; et al. (Frontiers in Plant Science, 2021)
Wheat stem rust disease caused by Puccinia graminis f. sp. tritici (Pgt) is a global threat to wheat production. Fast evolving populations of Pgt limit the efficacy of plant genetic resistance and constrain disease management strategies. Understanding molecular mechanisms that lead to rust infection and disease susceptibility could deliver novel strategies to deploy crop resistance through genetic loss of disease susceptibility. We used comparative transcriptome-based and orthology-guided approaches to characterize gene expression changes associated with Pgt infection in susceptible and resistant Triticum aestivum genotypes as well as the non-host Brachypodium distachyon. We targeted our analysis to genes with differential expression in T. aestivum and genes suppressed or not affected in B. distachyon and report several processes potentially linked to susceptibility to Pgt, such as cell death suppression and impairment of photosynthesis. We complemented our approach with a gene co-expression network analysis to identify wheat targets to deliver resistance to Pgt through removal or modification of putative susceptibility genes.